BOOK REVIEWS - Lategan, Bernard C. (Scriptura, 1983)
God, History and Historians: An anthology of Modern Christian Views of History / C T McIntire - Reviewed by: Bernard C Lategan. An Evaluation of Claims to the Charismatic Gifts / D Judisch; Images of the Spirit / M G Kline; The Holy Spirit / E Schweizer; The Spirit in Biblical Perspective / W S Forster - Reviewed by: J A Loubser. A Basic Introduction to the New Testament / Robert C Walton (ED) - reviewed by: J C Malan. The Living World of the Old Testament / Bernhard W Anderson - reviewed by: J C Malan. The Roots of Fundamentalism / Ernest R Sandeen; The Scope and Authority of the Bible (Explorations in Theology no 7) / James Barr - Reviewed by: W van Huyssteen; The Changing Continuity of Christian Ethics vol 2: the Insights of History / R E O White - Reviewed by: Johann Kinghorn.